Improving The Quality of Students' Learning in Fiqh Subjects of Hajj and Umrah Materials through Cooperative Script Learning Model - Mochammad Syafiuddin Shobirin; Mariatul Zulfa (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this research is to fulfill the final task and to find out the improvement of students' learning outcomes through cooperative script learning model in the subjects of fiqh of hajj and umrah materials in MA AL-BAIRUNY sambongdukuh jombang. The stages of researchers to obtain information begins with the presence of researchers to the location directly looking for data sources through observation methods, interviews and documentation. As a data collection step to find out how the learning process in MA AL-BAIRUNY sambongdukuh jombang. Based on the results of research MA AL-BAIRUNY sambongdukuh jombang has not implemented the cooperative script learning model and to improve student learning outcomes is to apply cooperative script learning model in class X in fiqh subjects through the first few stages are planning, implementation and evaluation. For the results of learning students are conducted with pretest and postest assessment based on the results of research obtained learning results through the cooperative script prison model